Inhibitory and Bactericidal Potential of Crude Acetone Extracts of Combretum molle (Combretaceae) on Drug-resistant Strains of Helicobacter pylori - Njume, Collise; Afolayan, Anthony J; Samie, Amidou; Ndip, Roland N (Journal of Health, Population and Nutrition, 2011)
Infection with Helicobacter pylori is strongly associated with a number of gastroduodenal pathologies. Antimicrobial resistance to commonly-used drugs has generated a considerable interest in the search for novel therapeutic compounds from medicinal plants. As an ongoing effort of this search, the susceptibility of 32 clinical strains of H. pylori and a reference strain—NCTC 11,638—was evaluated against five solvent extracts of Combretum molle, a plant widely used for the treatment of gastric ulcers and other stomach-related morbidities in South Africa. The extracts were screened for activity by the agar-well diffusion method, and the most active one of them was tested against the same strains by micro-broth dilution and time kill assays. Metronidazole and amoxicillin were included in these experiments as positive control antibiotics. The solvent extracts all demonstrated anti-H. pylori activity with zone diameters of inhibition between 0 and 38 mm. The most potent anti-H. pylori activity was demonstrated by the acetone extract, to which 87.5% of the clinical strains were susceptible. The minimum inhibitory concentration (MIC90) values for this extract ranged from 1.25 to 5.0 mg/mL while those for amoxicillin and metronidazole ranged from 0.001 to 0.94 mg/mL and from 0.004 to 5.0 mg/mL respectively. The acetone extract was highly bactericidal at a concentration of 2.5 and 5.0 mg/mL, with complete elimination of the test organisms in 24 hours. Its inhibitory activity was better than that of metronidazole (p<0.05) as opposed to amoxicillin (p<0.05). The results demonstrate that C. molle may contain therapeutically-useful compounds against H. pylori, which are mostly concentrated in the acetone extract. Key words: Acetone; Antibiotic resistance; Combretum molle; Crude extracts; Helicobacter pylori; Microbial sensitivity tests; Minimum inhibitory concentration; South Africa DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8897 JHPN 2011; 29(5): 438-445